Novel Functional Genes Involved in Transdifferentiation of Canine ADMSCs Into Insulin-Producing Cells, as Determined by Absolute Quantitative Transcriptome Sequencing Analysis - Dai, Pengxiu; Li, Jiakai; Chen, Yijing; Zhang, Luwen; Zhang, Xinke; Wang, Jinglu; Qi, Guixiang; Zhang, Yihua (Frontiers in Cell and Developmental Biology, 2021)
The transdifferentiation of adipose-derived mesenchymal stem cells (ADMSCs) into insulin-producing cells (IPCs) is a potential resource for the treatment of diabetes. However, the changes of genes and metabolic pathways on the transdifferentiation of ADMSCs into IPCs are largely unknown. In this study, the transdifferentiation of canine ADMSCs into IPCs was completed using five types of procedures. Absolute Quantitative Transcriptome Sequencing Analysis was performed at different stages of the optimal procedure. A total of 60,151 transcripts were obtained. Differentially expressed genes (DEGs) were divided into 5 groups: IPC1 vs. ADSC (1169 upregulated genes and 1377 downregulated genes), IPC2 vs. IPC1 (1323 upregulated genes and 803 downregulated genes), IPC3 vs. IPC2 (722 upregulated genes and 680 downregulated genes), IPC4 vs. IPC3 (539 upregulated genes and 1561 downregulated genes), and Beta_cell vs. IPC4 (2816 upregulated genes and 4571 downregulated genes).The Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis of DEGs revealed that many genes and signaling pathways that are essential for transdifferentiation. Hnf1B, Dll1, Pbx1, Rfx3 and Foxa1 were screened out, and the functions of five genes were verified further by overexpression and silence. Foxa1, Pbx1 and Rfx3 exhibited significant effects, can be used as specific key regulatory factors in the transdifferentiation of ADMSCs into IPCs. This study provides a foundation for future work to understand the mechanisms of the transdifferentiation of ADMSCs into IPCs and acquire IPCs with high maturity.